Biological activity of human-mouse IgG1, IgG2, IgG3, and IgG4 chimeric monoclonal antibodies with antitumor specificity. - Steplewski, Z (1988)
Chimeric antibodies were constructed in which the murine variable region of anti-colorectal cancer monoclonal antibody CO17-1A was joined with human gamma 1, gamma 2, gamma 3, and gamma 4 constant regions. Human-mouse chimeric proteins were compared with the parental murine IgG2a antibody CO17-1A for their ability to participate in tumor-cell destruction by human and murine effector cells in antibody-dependent cell-mediated cytotoxicity (ADCC) assays. All of the chimeric antibodies showed different degrees of ADCC with human lymphocytes, monocytes, and granulocytes and with murine macrophages. Monocytes and macrophages were able to utilize the chimeric IgG1 and, to a lesser degree, IgG4 and IgG3 antibodies to lyse tumor-cell targets in ADCC assays. The chimeric IgG1 and IgG4 antibodies were nearly as effective as the parental CO17-1A antibody in inhibiting tumor growth in nude mice. These data indicate that chimeric IgG1 antibody is superior in its antitumor activity.